Dual Role of CD4 in Peripheral T Lymphocytes - Glatzová, Daniela; Cebecauer, Marek (Frontiers in Immunology, 2019)
The interaction of T-cell receptors (TCRs) with self- and non-self-peptides in the major histocompatibility complex (MHC) stimulates crucial signalling events, which in turn can activate T lymphocytes. A variety of accessory molecules further modulate T-cell signalling. Of these, the CD4 and CD8 coreceptors make the most critical contributions to T cell sensitivity in vivo. Whereas CD4 function in T cell development is well characterised, its role in peripheral T cells remains incompletely understood. It was originally suggested that CD4 stabilises weak interactions between TCRs and peptides in the MHC and delivers Lck kinases to that complex. The results of numerous experiments support the latter role, indicating that the CD4-Lck complex accelerates TCR-triggered signalling and controls the availability of the kinase for TCR in the absence of the ligand. On the other hand, extremely low affinity of CD4 for MHC rules out its ability to stabilise the receptor-ligand complex. In this review, we summarise the current knowledge on CD4 in T cells, with a special emphasis on the spatio-temporal organisation of early signalling events and the relevance for CD4 function. We further highlight the capacity of CD4 to interact with the MHC in the absence of TCR. It drives the adhesion of T cells to the cells that express the MHC. This process is facilitated by the CD4 accumulation in the tips of microvilli on the surface of unstimulated T cells. Based on these observations, we suggest an alternative model of CD4 role in T-cell activation.